IMPLEMENTASI APLIKASI UJIAN DARING BERBASIS WEBSITE PADA SMA BUDI MULIA JAKARTA - Supriyanto Karya (Institut Bisnis dan Informatika Kwik Kian Gie, 2017)
Implementation of the exam in SMA Budi Mulia Jakarta still use conventional methods that require time, cost and considerable energy. The semester exam activity usually begins with the teacher of the subject making exam questions by hand writing, then the SAS (Student Administration System) will type and double the test of the student, then after the exam is completed, the teacher checks the student answer sheet one by one. Understanding the online exam is a test held by using the computer as the main media in conducting the exam. The Online Exam is a new innovation in the digital age of technology. Online exams are able to present an evaluation / exam system managed by a local server. In this case the research method used is a method by collecting and describing data about the state directly from the field and precisely the object of research to obtain data relevant. The system that is running at SMA Budi Mulia is described in the form of flowchart. The results of the design of online exam system that is running consists of several components diagram of the Contex Diagram Exam Oline Application, Use Case on Online Exams, Activity Diagram Making Problems and Activity Diagram Online Exam. The design of the menu structure contained in the online exam application. With the online exam application, the teacher of the field of study can type the exam of the student, the SAS (Student Administration System) that helps the teachers of the study field to type the student exam questions, and the correction of student answers will automatically enter into the system of student test results in the teacher's field of study.Keywords: Online Exam Application, Website, SAS (Student Administration System